PENGARUH POLA KERJA DAN MOTIVASI KERJA TERHADAP PERWIRA PEMELIHARA ALUTSISTA TNI ANGKATAN UDARA Studi kausal di Satuan Pemeliharaan TNI Angkatan Udara Jakarta 2010 - Subandijo Subandijo (JURNAL MITRA MANAJEMEN, 2012)
ABSTRACTThe objective of this research is to study the effect of the job design andwork motivation on the performance of the maintenance officers of the Airforce. Thisresearch was conducted at the maintenance unit of the Airforce in Jakarta. Themethod used to analyze this research is the causal study. The sample of thisresearch were 100 personnel of the maintenance officers of the aeronautical unitand maintenance unit that were selected randomly. From this research resultswere found that: (1) there is a direct effect of job design on performance; (2) there isa direct effect of work motivation on performance of the officers. According to thesefindings, it could be concluded that the performance of the officers were effected byjob design and work motivation. And the job design the most dominant effect toimprove the job performance of the officers. In other words, we can say that thehigher knowledge in the job design will improve the capability in the individualperformance of the officers.Finally it’s concluded that the job design and work motivation should beconsidered in improving job performance of the officers.Key Word: Job design, work motivation and performance of the officer